Study the Factors Affecting Maturity Level in UAE Information Technology Organizations - Dabash, Amro Naim Ali (2015)
UAE has invested immensely in IT and has become an acknowledged IT economy. Many initiatives undertaken by the government of UAE has made it renowned as a regional hub for IT services and manufacturing. However, there is need to establish internationally recognized industrial standards to provide both global recognition and a competitive edge to UAE IT organizations. CMMI is a well-established framework in the area of process maturity that details a list of prescribed process areas from levels 1-5. Some IT organizations in UAE are working towards CMMI implementation and achieving higher levels of maturity. A high score on CMMI maturity levels provides the required recognition and competitive advantages to organizations. However, CMMI awareness is low in UAE and only a handful of organizations have adopted it. CMMI implementation is also not well documented in the UAE and this field needs further research– to encourage and enhance CMMI adoption in UAE. This research identified the factors that affect the CMMI maturity levels in UAE organizations through secondary research – an extensive literature review and case studies. This research has been limited in scope due to the inadequate CMMI awareness in the UAE. A total of seven case studies were undertaken of which on two were from the Arab region. A single case study of Mercator of the Emirates Group in the UAE was also conducted, but the results were inconclusive due to scarcity of relevant data. Several factors were found to effect CMMI maturity levels in organization, of which two in particular were specific to the Arab region. These effective factors can be easily manipulated to the advantage of organizations implementing CMMI as has been demonstrated in the case studies examined by this research.